2009
DOI: 10.1093/ndt/gfp087
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery approach for endovascular salvage of occluded autogenous radial-cephalic fistulae

Abstract: An endovascular intervention through the radial artery approach is a safe and feasible strategy choice for restoring occluded autogenous radial-cephalic fistulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
3
29
1
Order By: Relevance
“…). This compares favorably with other reported smaller series ranging in size from 10 to 73 cases with a technical success rate from 59% to 100%. These reports documented a primary patency of 36% to 77%, 18% to 60%, and 18% to 70% at 3, 6, and 12 months, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…). This compares favorably with other reported smaller series ranging in size from 10 to 73 cases with a technical success rate from 59% to 100%. These reports documented a primary patency of 36% to 77%, 18% to 60%, and 18% to 70% at 3, 6, and 12 months, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…This implicates that optimal timing for PTA on the treatable lesions is crucial and early referral for PTA is a good policy as described in a couple of articles . Apart from the results of stenotic lesions, long lesions were associated with the poorer patency outcome as consistently shown in a few studies , despite insignificant differences in systolic RAPs observed between long and short lesions in the study. Furthermore, the distal RAP may become normalized or optimized when a successful PTA is achieved.…”
Section: Discussionsupporting
confidence: 57%
“…A radiocephalic AVF (RCAVF) constructed with an anastomosis of the radial artery and cephalic vein commonly results in juxta-anastomotic venous stenosis. Percutaneous transluminal angioplasty (PTA) is considered the first-line modality to manage the stenosis-related dysfunction (3,4,(9)(10)(11)(12)(13)(14)(15)(16). For RCAVF venous lesions, angiography-guided transradial PTA has been reported to be safe and effective (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall success rate achieved in this study (clinical success rate 93%; anatomic success rate of 91%) is similar to those reported previously. 38,[43][44][45][46] In keeping with the descriptive nature of this study, the emphasis was on feasibility and overall effectiveness of the endovascular procedures performed by the authors (MM, JPK and RB).…”
Section: Discussionmentioning
confidence: 99%